A Security Trending Review on Software Define Network (SDN) - Mohd Zafran Abdul Aziz; Koji Okamura (Journal of Advanced Research in Computing and Applications, 2023)
This work presents a comprehensive literature review on security for SDN. We revisit the existing works for network security in the SDN such as mitigation attack from D/DoS, botnet, spam etc. Later, we discuss the SDN and its hype cycle for emerging technologies. SDN offers a high level of network abstraction management as well as a centralized security solution. Due to robustness and flexibility of SDN architecture, many researchers have chosen SDN. It can help to prevent D/DoS attacks in a single SDN domain (e.g. LAN, WAN) or multiple integrated SDN domains (e.g. MAN). This review paper will drive a research topics on network security using SDN technologies. Various study on SDN communication and infrastructure, but this paper focuses more on network security based on technical analysis and machine learning using Artificial Intelligent. Based on research and development trending in the literature review, SDN is considered for the Gartner’s hype cycle for emerging technologies.